2023
DOI: 10.1002/jdd.13238
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the health gap: Measuring the unmet social needs of patients within a dental school clinic

Abstract: Objectives As safety‐net clinics, dental school clinics are uniquely positioned to evaluate the unmet social need. There is evidence that patients treated in a safety‐net type clinic, such as dental schools, report experiencing one or more of the determinants of health. However, there is limited evidence describing screening for Social Determinants of Health (SDOH) in dental clinics. The purpose of this study is to gain knowledge of the types of social determinants of health that exist in a dental school clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…For example, previous research found that it was possible to measure cardiac risk and dysglycemia in the dental setting. 15 , 16 The present study also complements a study led by Mays et al 34 that measured unmet social needs within a dental school clinic.…”
Section: Discussionsupporting
confidence: 69%
“…For example, previous research found that it was possible to measure cardiac risk and dysglycemia in the dental setting. 15 , 16 The present study also complements a study led by Mays et al 34 that measured unmet social needs within a dental school clinic.…”
Section: Discussionsupporting
confidence: 69%